Matching Linguistic Training with Individual Indigenous Community's Needs - Caffery, Jo (The Australian Journal of Indigenous Education, 2016)
Australia is rapidly losing its Indigenous multicultural and multilingual identity. This vast continent has lost 90 per cent of its Indigenous languages and cultures, without adequate documentation, and risks losing the rest by 2050 if action is not taken. There are formal, accredited linguistics courses designed specifically for Indigenous Australians to document and maintain their traditional languages. This research assessed the relevance of linguistic training for Indigenous Australians in remote communities and whether it provides the necessary skills for Indigenous Australians to document and maintain their languages in their particular workplace or community. The study found that Indigenous Australians come from a diversity of areas across the vast continent of Australia, live a diversity of lifestyles, have a diversity of linguistic attitudes and have access to different and often limited resources and support to meet their goals of documenting their endangered languages. As a result, standardised formal training is generally unlikely to provide the necessary linguistic skills needed for their particular community or workplace. However, by matching linguistic training with individual language community's linguistic situation, targeted training could increase the documentation of Australia's Indigenous languages.